Resurgence of the Birthright Citizenship Debate - Katherine Nesler (Washington University Journal of Law & Policy, 2017)
This Note explores the different conceptions of citizenship, jus solis (the right of birth) and jus sanguinis (the right of blood), and the implications related to current U.S. jurisprudence under the Fourteenth Amendment. In Part I of this Note, Nesler traces the history of the birthright citizenship debate and the opposing arguments. In Part II, the Author addresses the place birthright citizenship has had in the U.S. Fourteenth Amendment and its pivotal role from historical and cultural perspectives. Part III advocates for continued support for birthright citizenship in the U.S., but cautions it should not come before the U.S. Supreme Court unless the ideological split among the justices favors jus solis citizenship.
Keywords: Citizenship; Birthright Citizenship; Naturalization; Immigration; Fourteenth Amendment; Citizenship Clause; Undocumented Immigrants; Constitutional Amendments; U.S. Constitution